Ta’tsir At-Thariqah Al-Intiqaiyyah fi Maharah Al-Kalam li Ash-Shaf As-Sabi’ bi Ma’had Al-Anshar Batang Polo - Nur Khomisah Pohan; Nur Hasnah (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
The purpose of this research is to find out the effect of the selective method on the seventh grade speaking skill. The type of research is quantitative research using the experimental method. Quantitative research methods can be defined as methods in which research based on the philosophy of positivism is used to search for a specific population or sample. While the experimental method is an experimental design that has a control group, it is not fully functional to control variables beyond the variables affecting the experiment. As for the results of the research, the effect of the selective method on the seventh grade speaking skill is an overview of the data obtained by the researcher. The data generated from this study are the pre- and post-test values. Before being used as pre- and post-exam questions, the 30 multiple-choice questions were tested in Chapter 7. As for its results, I mean, there is an effect of the selective method on speaking skill at the “Al-Ansar” Institute, Batang Polo. The dimensional result is 49.55 and the dimensional result means 73.88 with a gain 0, 48 غرض هذا البحث لمعرفة  تأثير طريقة الانتقائية في مهارة الكلام الصف السابع. أما نوع البحث فهو البحث الكمي باستخدام طريقة التجربة.  يمكن تعريف طرق البحث الكمي على أنها طرق يتم استخدام البحث القائم على فلسفة الوضعية  للبحث عن مجتمع أو عينة معينة يتم أخذ العينات بشكل مجموع العينات، جمع البيانات  باستخدام أدوات البحث والتحليل بيانات  كمية/إحصائية بهدف الاختبار الفرضيات التي تم وضعها. بينما طريقة التجربة هي تصميم تجريبي التي لديها مجموعة تحكم،  لكنها لا تعمل بشكل كامل للتحكم في المتغيرات التي تتجاوز المتغيرات تؤثر على التجربة.وأما نتائج البحث تأثير طريقة الانتقائية في مهارة الكلام الصف السابع لمحة عامة عن البيانات  التي حصل عليها الباحثة.  البيانات  الناتجة عن هذه الدراسة هي قيم الاختبار القبلي والبعدي.  قبل استخدامها مثل أسئلة ما قبل الاختبار وبعدها، تم اختبار 30 سؤال اختيار من متعدد في الفصل السابع. وأما نتائجها يعني يوجد تأثير طريقة الانتقائية في مهارة الكلام بمعهد “الأنصار” باتأنغ بولو. بنتيجة البعدي 49،55 ونتيجة البعدي يعني 73،88 ب gain 0،48.